A Comparative Study on Risk Allocation for Different Procurement Type in Malaysian Industry. Issue 1 (1st October 2022) - Zainudin, Nurhuda Athira; Adnan, Hamimah; Azrin Baharuddin, Har Einur; Rosman, Muhammad Redza; Wan Ismail, Wan Norizan
Abstract: Risk allocation is one of the important aspects in risk management. However, there is a tendency that risks in construction are being allocated to parties that are least able to resist taking on the risk rather than parties that are more capable to manage the risks. There are different types of procurement that led to different approaches in settling risk allocation between contracting parties. This paper aims to identify risk allocation for different procurement types in construction projects focusing on traditional, design-build and public-private partnership procurement. For this research, a quantitative method was used, where 354 sets of questionnaires were distributed to selected construction firms in Klang Valley. Ninety-two (92) sets of questionnaires were returned and analyzed and the respondents were asked to rate the probability of risk occurrence. The result indicated that the top ranked risk factors are 'unstable government', 'delay in project approvals and permits', 'fluctuation of material cost', 'poorly written contract' and 'inadequate specification in contract'. The recommended risk allocation by respondent for each procurement is presented and found that client and contractor in Traditional procurement, the risks are allocate based on its nature of work. In Design-build, risk factors are mainly allocated to contractor. While in PPP, both contracting parties prefer the majority of the risk factors to be shared. The results of this research will assist practitioners in allocating risks to the party that most qualified to analyze, control, and manage these risks.